Analisis Pengaruh Biaya Promosi terhadap Nilai Penjualan Produk pada UD. Kopi Bali Banyuatis, Singaraja - DANE, N.; SUKAATMADJA, IPG.; BUDIASA, IW. (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2014)
Promotion is an activity undertaken various companies to communicate product advantages and persuade target customers to buy the product. Integration of a new integrated campaign using instruments to increase sales value and importance must be done in the form of an integrated process which is often called integrated marketing communications or integrated marketing communications (IMC), which includes the coordination of the various promotional elements and other marketing activities. Therefore, this study was designed to determine the role of promotion (promotion mix), which consists of the cost of advertising, sales promotion expenses, and the cost of public relations and news in influencing product sales value at UD. Kopi Bali Banyuatis Singaraja. The data used in this study is the cost of advertising, promotional costs, and the cost of public relations and news from the year 2007 to 2011. The data analysis technique used is multiple linear regression with SPSS version 17.0. The results showed simultaneous promotion mix variables have a positive and significant impact on the value of sales to the value of 0.001 p-value less than 0.05 level of significant and Fhitung value of 6.814 is greater than 2.769 Ftabel with determination coefficient 0.228 or 22.8 %. Partially, of the three variables promotional mix shows the cost of advertising and promotion costs are not significantly affected, while the public relations and news variables showed significant results. Most dominant variable affecting the value of sales is the cost of public relations and reporting the value of the standardized beta coefficient for 0412.
Keywords: promotional costs, sales value